Severe Sequelae to Mold-Related Illness as Demonstrated in Two Finnish Cohorts - Tuuminen, Tamara; Rinne, Kyösti Sakari (Frontiers in Immunology, 2017)
The presence of toxic indoor molds with accompanying bacterial growth is clearly detrimental to human health. The pathophysiological and toxicological effects of toxins and structural components of molds and bacteria have been clarified in experiments conducted in tissue culture and animals, and there is convincing epidemiologic evidence; nonetheless their implications for human health are either ignored or denied, at least in Finland. In this communication, we describe two cohorts suffering severe sequelae to mold-related illness. One cohort is a nine-member family with pets that moved into a new house, which soon proved to be infested with pathogenic molds. The other cohort consists of 30 teachers and 50 students from a mold-infested school building. The first cohort experienced a plethora of mucosal irritation, neurological, skin, allergic, and other symptoms, with all family members ultimately developing a multiple chemical syndrome. In the second cohort, we detected a greatly elevated prevalence of autoimmune conditions and malignancies. We claim that mold-related illness exists in multiple facets; if not simply a transient mucosal irritation or even an increased risk of asthma onset or its exacerbation. We propose a scheme to explain the natural course of the mold-related illness. We recommend that future studies should combine data from, e.g., cancer, autoimmune, and endocrine disorder registers and neurological and mental health or neuropsychological registers with mold-exposed individuals being monitored for prolonged follow-up times.